Repetition and practice. Developing mental training with young violinists: a collaboration - Vilnite, Fiona Mary; Marnauza, Mara (Frontiers in Psychology, 2024)
Mental training has been used successfully by professional musicians and athletes, yet rarely applied in pedagogical processes. As research in neuroscience can now explain how it connects to the processes of learning, its application and adaptation in pedagogy can now be explored. The aim of this mixed methods study was to investigate concepts of repetition and practice with mental training, and discuss adaptations for young violinists, to include attention, awareness, and creative musicality. Three exercises were developed with nine students (average age 8). The first involved creation of imagery, followed by physical practice; the second alternated mental imagery with physical practice; the third involved concurrent use of physical practice and mental imagery. Results of the first exercise indicate heightened awareness of technical skill; self-discovery of bow control, speed and distribution, tone production improvements and an ability to sustain longer notes post-mental training (Z = -2.666, p = 0.008 and Z= -2.670, p = 0.008). Observations from the second and third exercises include student experimentation with concepts of musical interpretation, an eagerness to repeat repertoire (≥ 5 times) and increased self-awareness of technical and musical accomplishments. The research suggests that mental training can be adapted for younger learners, that it encourages collaboration in the pedagogical process, develops student self-awareness of the cognitive and physical processes of violin playing.